2023
DOI: 10.1097/hc9.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Increasing national trend of direct-acting antiviral discontinuation among people treated for HCV 2016–2021

Abstract: Background: Direct-acting antiviral (DAA) treatment discontinuation may negatively impact HCV elimination efforts. In Australia, DAA therapy is pharmacy dispensed, generally in 4-week amounts, with the approved duration (8–24 wk) and volume dispensed reported in pharmaceutical administrative data. This analysis assessed national HCV treatment discontinuation. Methods: Individuals commencing DAAs between 2016 and 2021 were assessed for treatment discontinuation. Individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…An Australian study assessed trends of DAA discontinuations and HCV retreatment at the national level. 44 Data on treatment and retreatment were collected from administrative records provided by the Australian Pharmaceutical Benefit Scheme (PBS). For the PBS analysis, treatment discontinuation was defined as “1 or more repeat authorized prescription courses (28 [day] supply) not dispensed”; early discontinuation was defined as “discontinuing after the first 28 days of the treatment course had been dispensed”; late discontinuation was defined as “discontinuing after 56 days or more had been dispensed”; and retreatment was defined as “the commencement of a different DAA regimen any time after the end of the initial treatment date or the same DAA regimen ≥28 days after the last dispensation of the initial treatment.” Among 88,986 patients infected with HCV, 9% discontinued DAA treatment.…”
Section: Available Evidence Of Daa Adherence On Hcv Cure By Treatment...mentioning
confidence: 99%
See 1 more Smart Citation
“…An Australian study assessed trends of DAA discontinuations and HCV retreatment at the national level. 44 Data on treatment and retreatment were collected from administrative records provided by the Australian Pharmaceutical Benefit Scheme (PBS). For the PBS analysis, treatment discontinuation was defined as “1 or more repeat authorized prescription courses (28 [day] supply) not dispensed”; early discontinuation was defined as “discontinuing after the first 28 days of the treatment course had been dispensed”; late discontinuation was defined as “discontinuing after 56 days or more had been dispensed”; and retreatment was defined as “the commencement of a different DAA regimen any time after the end of the initial treatment date or the same DAA regimen ≥28 days after the last dispensation of the initial treatment.” Among 88,986 patients infected with HCV, 9% discontinued DAA treatment.…”
Section: Available Evidence Of Daa Adherence On Hcv Cure By Treatment...mentioning
confidence: 99%
“…46 47 Furthermore, Carson et al demonstrated that short-duration therapies may promote fewer treatment discontinuations. 44 It is important to identify poor adherence and consider using more “forgiving” medications when optimal adherence appears unlikely. 46 In practice, strategies to improve adherence should vary based on the patient population and factors that contribute to lower SVR rates.…”
Section: Best Practices For Evaluating and Improving Adherencementioning
confidence: 99%